Factors Associated with the Odds of Pregnancy for Dairy Cattle after Treatment of Ovarian Disorders in Northern Vietnam - S. T. Long; N. C. Toan; P. V. Gioi; P. T. Hang (Faculty of Animal Science, Bogor Agricultural University, 2022)
The study was carried out to assess factors related to the odds of pregnancy for dairy cattle after treating ovarian disorders in some Northern Vietnamese provinces. A total of 449 ovarian-disordered heifers and cows were given appropriate treatments for their diseases and were diagnosed by rectal palpation with pregnant status after artificial insemination. Data collected from ruminants were analyzed by applying Binary Logistics Procedure in SAS 9.0 and three methods were utilized to test the significant level of regressive coefficients related to the factors, which included various nutritional, environmental, and management factors (locations, parities, ages, body condition scores, housing types, mineral licking block diets, rubber bedding, and categories of disordered ovaries). Based on the odds ratio, cows and heifers in Ha-Noi zone had higher odds of pregnancy than in Vinh-Phuc province (odds ratio [OR] =1.97, p<0.05). Multiparous cows were likely to get a lower chance to conceive than heifers. The odds of pregnancy for dairy cattle decreased with the increase of age, and with each month increased of age, the odds of pregnancy decreased by 1.8%. The better housing condition the dairy cattle live in, the higher pregnancy rate they get. The pregnant opportunity of the dairy cattle kept in the concrete floor house is higher than that kept in rubber floor house (OR=4.03; p<0.0001). Adding mineral licking block in their diet affected the conception odds but did not affect BCS. When the appropriate treatment was used, dairy cattle with inactive ovaries were less likely to conceive than those with cystic ovarian disease and persistent corpus luteum.